Risk factors of large for gestational age among pregnant women with gestational diabetes mellitus: a protocol for systematic review and meta-analysis - Yinhua Su; Fuliang Shangguan; Huixi Yu; Zhongyu Li; Yingni Liang; Weilei Dong; Hanbing Li; Jiayu Shen (BMJ Open)
Introduction Women with gestational diabetes mellitus (GDM) are more likely to give birth to large for gestational age (LGA) infants, due to abnormalities in glucose metabolism during pregnancy. Although previous studies have explored the risk factors for LGA delivery in GDM women, the results are quite different and still lack of unified understanding.Objective To explore the elements linked to LGA delivery in GDM women, and thus provide a reference for medical staff to formulate relevant clinical interventions.Methods and analysis Systematic search of seven electronic databases (PubMed, Scopus, Cochrane Library, Web of Science, EMBASE, OVID and CINAHL) will be undertaken between the inception of the database to 1 August 2024. Quantitative studies published in English and focused on the risk factors for LGA delivery in GDM women will be included. Two researchers will independently screen the literature and any disagreements will be resolved by a third-party researcher. Joanna Briggs’s Institutional Critical Appraisal Tools will be used for the quality assessment of included studies. RevMan V.5.4 software will be used for data processing and summarising. To ensure the reliability and stability of the results, Q test and I2 test will be used to identify the heterogeneity between studies, while subgroup analysis and sensitivity analysis will be performed based on study quality.Ethics and dissemination This systematic review and meta-analysis will be based on published literature, and the findings will be published in a peer-reviewed journal and presented at major conferences focused on clinical nursing.PROSPERO registration number CRD42024559013.